The problem of uveitis in Bendel State of Nigeria: experience in Benin City. - Ayanru, J. O. (Br J Ophthalmol, 1977)
A review of 1987 patients with uveitis seen over an 11-year period in Bendel State of Nigeria has been undertaken; 56% of cases had a posterior/mid-peripheral uveitis, 15.1% a panuveitis, 21.5% an anterior uveitis. Acute anterior uveitis with classical symptoms was rarely seen. Its comparative rarity is presumably due to the absence of HL-A27 in Africans and altered immunological states from malaria and parasitic infections. Identified aetiological factors in anterior uveitis were leprosy (1 patient), tuberculosis (1 patient), herpes zoster (16 patients), and onchocerciasis (3 patients). The great majority of cases of posterior uveitis were of presumed toxoplasmic origin. Further studies are needed to demonstrate its mode of transmission in a population in which toxoplasmosis is endemic. Forest onchocerciasis is not a major cause of uveitis in southern Nigeria in the same way as savanna onchocerciasis is in northern Nigeria. Syphilis seems to play no part in the causation of uveitis in southern Nigeria. Better diagnostic facilities are required to determine the role of sarcoidosis and other possible causative factors. Uveitis is a major cause of blindness in Nigeria.